The Hope diamond, cursed objects, and unexplained artifacts - Coddington, Andrew (Paranormal investigations., 2018)
Examines the "curses" of several objects in history, and suggests possible scientific explanations. Includes images and illustrations, sidebars, a glossary, sources for further learning, and an index.